2022
DOI: 10.3390/molecules27103045
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Constituents of Diaphragma Juglandis Fructus and Their Inhibitory Effect on α-Glucosidase Activity

Abstract: In our current investigation, 37 constituents (1–37), including 11 megastigmanes (1–11), 17 flavonoids (12–28) and 9 phenylpropanoids (29–37), were isolated from a 70%-EtOH extract of Diaphragma juglandis Fructus. Among them, compounds 1–3, 12 and 29 were new compounds and their structures were elucidated on the basis of physicochemical evidence and meticulous spectroscopic analysis (NMR, HRESIMS and CD). Compounds 13, 16, 21 and 28 showed moderate inhibitory effect on α-glycosidase inhibitory activities, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The butanolic and hydroalcoholic extracts with the most potent antioxidant activity against DPPH also show the strongest inhibition of α-glucosidase better than acarbose, with IC50 values equal to 11.66 ± 1.21 µg/mL and 16.17 ± 0.24 µg/mL, respectively, (p < 0.05), and this means that the antioxidant activity can impact the anti-diabetic property of our extract. In their study, Tan et al report that the compound isolated from EtOH 70% walnut extract, especially flavonoids, shows a significant αglucosidase inhibitory activity (α-GIA), which can justify and support our results [113] .…”
Section: α-Glucosidase Inhibitory Activitysupporting
confidence: 85%
“…The butanolic and hydroalcoholic extracts with the most potent antioxidant activity against DPPH also show the strongest inhibition of α-glucosidase better than acarbose, with IC50 values equal to 11.66 ± 1.21 µg/mL and 16.17 ± 0.24 µg/mL, respectively, (p < 0.05), and this means that the antioxidant activity can impact the anti-diabetic property of our extract. In their study, Tan et al report that the compound isolated from EtOH 70% walnut extract, especially flavonoids, shows a significant αglucosidase inhibitory activity (α-GIA), which can justify and support our results [113] .…”
Section: α-Glucosidase Inhibitory Activitysupporting
confidence: 85%
“…Most of the reviewed studies reported the usage of WS in powder form, following the preparatory grinding of plant material. The extractions were conducted in ethanol [ 20 , 22 , 38 , 40 ] or methanol [ 26 , 27 , 32 ] at various concentrations, as well as in solvent mixes such as acetone:water [ 24 ], acetone:acetonitrile [ 25 ], and acetone:cyclohexane [ 27 ]. The extraction methods were generally based on ultra-turrax homogenization and stirring [ 24 ], vibrating [ 25 ], ultrasonic extraction [ 26 , 27 , 37 ], condensation and reflux, or enzyme-assisted extraction [ 32 ], then centrifugation, solvent evaporation, and lyophilization.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…The reviewed studies used various chromatographic techniques for identifying phenolic compounds: liquid chromatography-mass spectrometry (LC-MS) [ 24 ], liquid chromatography with tandem mass spectrometry (LC-MS/MS) [ 32 ], high-performance liquid chromatography (HPLC) [ 20 , 22 , 26 , 37 , 38 ], or ultra-performance liquid chromatography (UPLC) differently equipped: UPLC-MS (17), UHPLC-Q-Orbitrap coupled with high-resolution mass spectrometry HRMS [ 27 ], or UPLC-Q-Exactive Orbitrap MS [ 40 ].…”
Section: Phytochemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations